Ionospheric density perturbations recorded by DEMETER above intense thunderstorms. Issue 8 (8th August 2013) - Parrot, M.; Sauvaud, J. A.; Soula, S.; Pinçon, J. L.; van der Velde, O.
Abstract: [1] DEMETER (Detection of Electromagnetic Emissions Transmitted From Earthquake Regions) was a three‐axis stabilized Earth‐pointing spacecraft launched on 29 June 2004 into a low‐altitude (710 km) polar and circular orbit that was subsequently lowered to 650 km until the end of the mission in December 2010. DEMETER measured electromagnetic waves all around the Earth, except in the auroral zones (invariant latitude >65°). The frequency range for the electric field was from DC up to 3.5 MHz, and for the magnetic field, it was from a few hertz up to 20 kHz. At its altitude, the phenomena observed on the E field and B field spectrograms recorded during nighttime by the satellite in the very low frequency range are mainly dominated by whistlers. In a first step, the more intense whistlers have been searched. They correspond to the most powerful lightning strokes occurring below DEMETER. Then, it is shown that this intense lightning activity is able to perturb the electron and ion densities at the satellite altitude (up to 133%) during nighttime. These intense lightning strokes are generally associated with transient luminous events, and one event with many sprites recorded on 17 November 2006 above Europe is reported. Examining the charged particle precipitation, it is shown that this density enhancement in the high ionosphere can be related to the energetic particle precipitation induced by the strong whistlers emitted during a long‐duration thunderstorm activity at the same location. Key Points: Enhancement of electron density in the ionosphere above thunderstorms Enhancement of density due to lightning‐induced electron precipitation Winter thunderstorms with increasing number of sprites